2019
DOI: 10.1007/s12149-019-01408-y
|View full text |Cite
|
Sign up to set email alerts
|

111In-labeled anti-cadherin17 antibody D2101 has potential as a noninvasive imaging probe for diagnosing gastric cancer and lymph-node metastasis

Abstract: Objective Cadherin-17 (CDH17) is a transmembrane protein that mediates cell-cell adhesion and is frequently expressed in adenocarcinomas, including gastric cancer. CDH17 may be an effective diagnostic marker for the staging of gastric cancer. Here, we developed an 111 In-labeled anti-CDH17 monoclonal antibody (Mab) as an imaging tracer and performed biodistribution and single-photon emission computed tomography (SPECT)/computed tomography (CT) imaging studies using mice with CDH17-positive gastric cancer xenog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…Consistent with published studies, TMA data in the present study showed that 66% of gastric cancer samples express CDH17. The aberrant expression has resulted in the attempts to use CDH17 as a target for cancer imaging and therapy [ 22 , 39 , 40 ]. In the present study, we identified two nanobodies specifically bound to CDH17 and E8 nanobody was extensively explored for gastric cancer imaging and targeted therapy due to its relatively higher affinity (~ 70 nM).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with published studies, TMA data in the present study showed that 66% of gastric cancer samples express CDH17. The aberrant expression has resulted in the attempts to use CDH17 as a target for cancer imaging and therapy [ 22 , 39 , 40 ]. In the present study, we identified two nanobodies specifically bound to CDH17 and E8 nanobody was extensively explored for gastric cancer imaging and targeted therapy due to its relatively higher affinity (~ 70 nM).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated expression of genes such as ABCC5 [50], LRFN1 [59], ELOVL6 [58], and HTR2B [61] have been associated with metastasis in other cancer types. Recently, PET-based detection and monitoring of metastasis cancer has utilized the following antibodies: 111 In-labeled anti-CDH17 (gastric cancer) [114], 177 Lu-labeled anti-CD55 (lung cancer) [115], and radio-labeled anti-ERBB2 (various labeling, including 89 Zr, 64 Cu, 111 In) (breast cancer) [116]. The gene FOLH1 (folate hydrolase 1) is of particular interest since it codes for the transmembrane metalloenzyme PSMA (prostate-specific membrane antigen).…”
Section: Discussionmentioning
confidence: 99%
“…ImmunoPET and immunoSPECT have been used for the non-invasive imaging of gastric cancer in both preclinical and clinical studies. The first section of the review will discuss the use of immunoPET in GC targeting the antigens carcinoma-associated antigen (MG7) [ 14 ], programmed death-1 (PD-1) [ 16 ], cadherin-17 (CDH17) [ 15 ], human epidermal growth factor receptors 2 and 3 (HER2 [ 5 , 9 , 21 , 22 , 23 , 24 ] and HER3 [ 12 ]), hepatocyte growth factor (HGF [ 11 ]), and the mesenchymal-epithelial transition factor (MET) [ 10 ]. As shown in Table 1 , FDA-approved or newly developed antibodies targeting membrane antigens were radiolabeled with gallium-68 ( 68 Ga), technetium-99m ( 99m Tc), indium-111 ( 111 In), copper-64 ( 64 Cu), zirconium-89 ( 89 Zr), and bromine-76 ( 76 Br) and used for PET or SPECT imaging of gastric tumors.…”
Section: Immunopet and Immunospect With Full-length Antibodies In mentioning
confidence: 99%
“…In a healthy adult, the gene that codes for the CDH17 protein is silenced; however, it is often expressed in gastric cancer, as well as other adenocarcinomas. In a recent study, the potential of CDH17 as a biomarker in GC was investigated through imaging techniques [ 15 ]. The anti-CDH17 monoclonal antibody D2101 was radiolabeled with indium-111 and administered to mice with AGS gastric xenografts.…”
Section: Immunopet and Immunospect With Full-length Antibodies In mentioning
confidence: 99%
See 1 more Smart Citation